Neocolonization, machine and decolonization: the Odebrecht case - Paniagua Gutiérrez, Edwin Rafael (Razón y fe, 2021)
In this article, we will propose that decolonization, nowadays, rather than violence, implies the dismantling of the colonizing machine. For this, we will refer to the economic and commercial dimension of neocolonization, based on the case of the Brazilian construction company Odebrecht (multinational). Hence, our proposal will arise that, in post-colonial democracies, institutions (especially Justice) are called to play a leading role. The methodology we have followed is to analyze the concepts of The island that is repeated (Benítez Rojo) and The condemned of the Earth (Fanon), as well as several reports of the prosecution of the Odebrecht case.